Association between ABO blood groups and Müllerian anomalies: a single-center cohort study of 16,690 infertile women - Meghil, Saleh; Al-Bdairi, Adnan A.; Makki Al-Hindy, Hayder Abdul-Amir; Khdhair, Sallama H.; Shawki, Osama; Alkhalidi, Batool; Kareem, Hadeel K. (Pharmakeftiki, 2025)
This study investigated the relationship between ABO blood groups and Müllerian anomalies in infertile women evaluated at the Teba Infertility Center (TIC) in Babylon, Iraq. Conducted over a three-month period beginning in August 2024, the study retrospectively included infertile couples who attended TIC between 2016 and 2022. A total of 1,215 archived records were reviewed from among 16,690 infertile females diagnosed with Müllerian uterine anomalies. Comprehensive patient reports were compiled, and three-dimensional (3D) sonographic examinations were performed in order to classify uterine morphology according to the standards of the European Society of Human Reproduction and Embryology / European Society for Gynaecological Endoscopy (ESHRE/ESGE). All participants were assessed for ABO blood group and Rhesus (Rh) factor positivity in order to explore potential associations with specific uterine anomalies. Statistical analyses were conducted using the SPSS software, applying frequency and percentage distributions, mean values with standard deviations, and comparative tests for non-normally distributed and categorical variables. The findings revealed significant associations between ABO blood groups and the presence of Müllerian anomalies. Notably, individuals with blood group O exhibited a higher prevalence of these abnormalities. These results underscore the relevance of ABO typing in reproductive health assessments and suggest that women with specific blood group profiles may benefit from targeted diagnostic and clinical interventions. Further research is warranted in order to validate these associations and elucidate the underlying biological mechanisms.